Mesotherapy for local fat reduction. Issue 10 (25th June 2013) - Jayasinghe, S.; Guillot, T.; Bissoon, L.; Greenway, F.
Summary Mesotherapy, which is the injection of substances locally into mesodermally derived subcutaneous tissue, developed from empirical observations of a French physician in the 1950s. Although popular in Europe for many medical purposes, it is used for local cosmetic fat reduction in the United States. This paper reviews manuscripts indexed in PubMed/MEDLINE under 'mesotherapy', which pertains to local fat reduction. The history of lipolytic mesotherapy, the physiology of body fat distribution, the mechanism of action of different lipolytic stimulators and their increased efficacy in combination are reviewed. Mesotherapy falls into two categories. Lipolytic mesotherapy using lipolytic stimulators requires more frequent treatments as the fat cells are not destroyed and can refill over time. Ablative mesotherapy destroys fat cells with a detergent, causes inflammation and scarring from the fat necrosis, but requires fewer treatments. The historic and empiric mixing of sodium channel blocking local anaesthetics in mesotherapy solutions inhibits the intended lipolysis. Major mesotherapy safety concerns include injection site infections from poor sterile technique. Cosmetic mesotherapy directs the area from which fat is lost to improve self‐image. Studies were of relatively small number, many with limited sample sizes. Future research should be directed towards achieving a Food and Drug Administration indication rather than continuing expansion of off‐label use.